Emergency Remote Teaching and Learning in Portugal: Preschool to Secondary School Teachers' Perceptions - Filipa Seabra; António Teixeira; Marta Abelha; Luísa Aires (MDPI AG, 2021)
Emergency remote teaching and learning (ERTL) represent a critical and challenging time for teachers globally. To understand how Portuguese teachers interpreted their ERTL experiences of the first lockdown, we started by asking: What perspectives do teachers have about ERTL? Answering three open questions made available online between April and May of 2020, a sample of 305 preschool, basic, and secondary school teachers expressed their perspectives on (i) difficulties throughout ERTL; (ii) students' constraints in participating in ERTL; (iii) the potential and benefits resulting from this exceptional period. Data were analyzed using content analysis. While Portuguese teachers perceived ERTL with concern, a majority also saw it as an opportunity. Workload, work conditions, and time management were the most frequently mentioned difficulties. Regarding students' constraints, teachers emphasized participation, the role of parents, lack of contact, and autonomy. Despite the constraints and difficulties, teachers highlighted gains such as the development of digital competencies and the opportunity to transform teaching and learning. Only 18 teachers suggested there were no positive outcomes from this experience. Since this is an exploratory study, further studies are needed to triangulate the findings.